Corporate Governance with the Institutional Theory Approach on Regional Development Banks in Indonesia - Umanto, Umanto; Wijaya, Chandra; Atmoko, Andreo Wahyudi (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2016)
The purpose of this research paper is to analyze the implementation of corporate governance at the Regional Development Banks, or locally known as Bank Pembangunan Daerah, in Indonesia. The focus of this study is on the role and the position of the governing body or board as well as the relations between governance in micro context and macro condition in the framework of institutional theory. The kind of paradigm that is used in this research paper is the post-positivist paradigm by using mixed methods. To analyze the implementation of corporate governance, this research paper is using several key actors: BOD's Size, Board of Commissioners Size, Board of Independent Commissioners Size, Audit Committee's Size, Block-holder Ownership, Risk Monitoring Committee, and Nomination and Remuneration Committee. The results of this research paper indicate that Bank Pembangunan Daerah merely fulfill the requirements of important tools in the implementation of corporate governance. In the end, this will influence the manageability of risk management and compliance process. This condition has positioned the importance of the existence of board in the form of both board of commissioners and board of directors in the management and the achievements of the performance of Bank Pembangunan Daerah (BPDs). In the perspective of corporate governance theorizing that is related to the institutional approach, board can be the balancing power in the context of the diversity of agents that display the relationship patterns not only in the micro-level that involve principal, management, and employees, but also in the macro condition such as legal system in the forms of regulations, social and cultural system, and political system in the form of relations between companies and both legislative and executive institutions. This is related to the strong influence of bureaucracy and political institutions that demonstrate the emergence of conflicting objectives and political interference in the management of Bank Pembangunan Daerah. This condition emerges as the consequences of the existence of Bank Pembangunan Daerah as regional-owned enterprises (BUMDs) that has dual functions, namely as a business enterprise that focuses on making profits as well as an agent of regional development and providing services to the public.